Enchanted Archive: Influence, Dissemination, and Media Transformation in Shelley’s “Ode to the West Wind” - Sympos, Roman (Romanticism and Victorianism on the Net, 2008)
AbstractIn “Ode to the West Wind” Percy Shelley represents the instability of the archive and the tenuousness of literary transmission through allusions, via Dante’s Divine Comedy and Virgil’s Aeneid, to a formative period in the history of the book: the period from roughly the first century BCE to the fourth century CE when the classical volumen or scroll was giving way to the codex of cut and sewn pages or “leaves.” By registering the poet’s own anxieties over the survival of his poetry and the perils of fragmentary dissemination through the image of “leaves dead” by which his two great precursors imagined the afterlives of departed souls, Shelley’s prophetic ode speaks to our own anxieties over the possibility of archival displacement and dispersion in a digital age while reaching back two millennia to the re-establishment of state religion, transformations in writing practices, and the founding myth of the Cumaen Sybil in Augustan Rome.